THE DISRUPTION OF HUMANITARIAN INNOVATIONS IN THE SPACE OF GLOBAL INFORMATION NETWORKS - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article investigates the contents of humanitarian innovations in postmodern culture. Relying on the fact that the innovative activities in the information age is a social need, the author puts a question about the nature of human innovations. In the space of global information networks humanitarian innovations turn to their socio-cultural media capacity and the main source of social information broadcast